Predatory Masculinities: A Gendered Re-reading of Ted Hughes’s Hawk Roosting - Ghosh, Arun Kumar (International Journal of Research in Interdisciplinary Studies, 2025)
This study re-examines Ted Hughes’s Hawk Roosting through the prism of gender theory, arguing that the poem enacts a distinct mode of predatory masculinity embedded within its language, symbolism, and ideological posture. Traditionally interpreted as a poetic embodiment of political tyranny, individual ego, or natural instinct, the hawk’s monologue has rarely been investigated in relation to the cultural scripts of masculine authority it performs. Addressing this lacuna, the present paper analyses how Hughes’s representation of predation intersects with post-war British anxieties surrounding power, violence, and the naturalisation of hierarchical control. Drawing upon close reading, discourse analysis, eco-masculinity studies, and contextual literary history, the research contends that the hawk’s voice stages a form of hypermasculine identity characterised by sovereign self-authorization, vertical dominance, and uncompromising territoriality. The findings reveal that Hughes neither straightforwardly condemns nor glorifies such masculinity; instead, the poem deliberately holds readers within an uneasy tension between natural behaviour and ideological aggression. The discussion extends this argument by situating predatory masculinity within broader ecological and ethical debates. The study concludes by outlining avenues for future scholarship within eco-gender criticism and modern British poetry.